(untitled) (UUM Journal of Legal Studies, 2020)
The constitution confers on the legislative arm of government impeachment power and prescribes when and how it should be exercised. Disputes arising from the exercise of this power are submitted to the courts for adjudication in line with their inherent powers. The issue of compliance with these constitutional requirements is a cause for concern as most of the impeachment proceedings conducted so far in Nigeria had been challenged in court for noncompliance. The question is, could this role played by the Nigerian courts ensure compliance? The objective of this paper is, therefore, to determine whether the courts could ensure compliance with the constitutional requirement for impeachment. In order to achieve the objective of this paper, doctrinal methodology is used whereby relevant materials were analyzed and conclusion made. The result showed that the role played by the courts cannot ensure compliance with the constitutional requirements because the courts only intervene after the conclusion of the exercise due to disrespect to court orders from the legislature. This is largely due to lack of specific role conferred on the courts in impeachment proceedings. It is, therefore, recommended that the constitution be amended to vest on the Supreme Court the specific role of ensuring that all the constitutional requirements for impeachment have been duly complied with before a public officer is removed.